The short- and long-run effects of medical malpractice lawsuits on medical spending and hospital operations in China - Gordon Liu; Junjian Yi; Ye Yuan; Shaoyang Zhao (Journal of Comparative Economics, 2023)
China is experiencing a surge in medical malpractice lawsuits. Using administrative hospital panel data, this paper investigates both short- and long-run impacts of medical malpractice lawsuits on patient medical spending and hospital operations. We find that after the occurrence of an additional malpractice lawsuit in a hospital, total medical spending per patient visit increases by 2.8% in the current year and by as much as 8.8% in the long run. This increase is mainly driven by spending on prescription drugs and diagnostic tests. In response, hospitals invest more in medical devices and procure more drugs. We find little evidence of changes in patient outcomes. Our findings show that the surge of medical malpractice lawsuits leads to defensive medicine and fuels the secular growth of medical spending in China.